Synthesis, Characterization, and Spectroscopic Properties of Hexa(4-Bromo-2-Formyl-Phenoxy)Cyclotriphosphazene and Hexa(4-Chloro-2-Formyl-Phenoxy)Cyclotriphosphazene and Fully Substituted Cyclotriphosphazene Derivatives Bearing a Schiff Base at Room Temperature - Ozturk, Ali Ihsan; Aslan, Fatih; Yilmaz, Okkes; Algin, Mehmet; Arslan, Mustafa; Mutlu, H. Ibrahim (Taylor & Francis Ltd, 2013)
Hexa(4-bromo-2-formyl-phenoxy)cyclotriphosphazene (2) and hexa(4-chloro-2- formyl-phenoxy)cyclotriphosphazene (3) were obtained from the reactions of hexachloro- cyclotriphosphazene (1) with 5-bromosalicylaldehyde and 5-chlorosalicylaldehyde in the presence of (C2H5)(3)N and K2CO3 at room temperature, respectively. The new two organocyclotriphosphazenes bearing formyl groups were reacted with 4-cyano aniline, 2-phenyl aniline, 4-aceto aniline, 5-chloro-2-hydroxy aniline, 2-hydroxy aniline, 4-hydroxy aniline, 2-(4-morpholino)ethyl amine, 4-carboxy aniline, 4-carbomoyl aniline, 2-mercapto aniline, and 5-amino isoquonoline to prepare cyclotriphosphazene derivatives containing a Schiff base at room temperature. However, fully phenoxy-substituted cyclotriphosphazenes containing a Schiff base were isolated from the reactions of the compound 2 and 3 with 5-chloro-2-hydroxy aniline, 2-hydroxy aniline, 4-hydroxy aniline, and 2-(4-morpholino)ethyl amine. The structures of the synthesized compounds were characterized by elemental analysis, IR, and NMR (H-1, C-13, P-31) spectroscopy. According to the results of the analysis, all synthesized compounds were found to be fully substituted organocyclotriphosphazenes, such as hexa[4-bromo-2-(5-chloro-2-hydroxy-pheyliminomethyl)phenoxy]cyclotriphosphaze (2a). All cyclotriphosphazene derivatives synthesized gave fluorescence emission peaks in range between 300nm and 410nm.
Keywords: Phosphazene; cyclotriphosphazene; organophosphazene; hexacholorocyclotriphosphazene; salicylaldehyde; Schiff base